2023
DOI: 10.1136/spcare-2022-003931
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivors–supportive care needs: systematic review

Abstract: ObjectivesTo achieve optimal survival care outcomes, all healthcare services must be tailored to patients’ specific needs, preferences and concerns throughout the survival period. This study aimed to identify supportive care needs from the point of view of breast cancer survivors.MethodsFollowing the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for reporting systematic reviews, a comprehensive search of PubMed, Web of Science and Scopus was performed. The inclusion criteria wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…A scoping review is recommended to comprehensively assess the breadth of the research topic and identify gaps worthy of further investigation (Pollock et al, 2021;Tricco et al, 2016). Several reviews have been conducted on this topic (Fan et al, 2023;Fiszer et al, 2014;Khajoei et al, 2023;Wabula et al, 2020). A systematic review of 23 quantitative studies examined the prevalence and factors associated with unmet care needs in women with breast cancer (Fiszer et al, 2014).…”
Section: The Rationale For a Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review is recommended to comprehensively assess the breadth of the research topic and identify gaps worthy of further investigation (Pollock et al, 2021;Tricco et al, 2016). Several reviews have been conducted on this topic (Fan et al, 2023;Fiszer et al, 2014;Khajoei et al, 2023;Wabula et al, 2020). A systematic review of 23 quantitative studies examined the prevalence and factors associated with unmet care needs in women with breast cancer (Fiszer et al, 2014).…”
Section: The Rationale For a Scoping Reviewmentioning
confidence: 99%
“…Similarly, a systematic review included 16 studies with a search timeframe from 2014 to 2020 (Wabula et al, 2020); however, that systematic review did not incorporate a critical appraisal process, which limited its robustness and generalisability. Another systematic review comprehensively examined the domains and subdomains of unmet care needs, utilizing a narrative synthesis to present several essential needs and provide clinical implications (Khajoei et al, 2023). However, these reviews did not show the research advancements and identified gaps that warrant further investigation.…”
Section: The Rationale For a Scoping Reviewmentioning
confidence: 99%
“…1 Specifically, breast cancer stands out as one of the most prevalent cancer types and holds the primary position among all cancers diagnosed in women globally (24.5%). 2 High incidence and mortality rates cause the studies on the treatment of this disease to increase everyday. 3 Presently, while surgical resection, chemotherapy, and radiotherapy are employed in the management of breast cancer, there is still no conclusive treatment available to proactively prevent the onset of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is an important disease with a high mortality rate which causes changes in the normal cell cycle by uncontrolled division of cells . Specifically, breast cancer stands out as one of the most prevalent cancer types and holds the primary position among all cancers diagnosed in women globally (24.5%) . High incidence and mortality rates cause the studies on the treatment of this disease to increase everyday …”
Section: Introductionmentioning
confidence: 99%
“…The need for help in dealing with problems such as financial distress [ 14 ], Pain [ 15 ], Memory problems [ 16 ], Fear of disclosure [ 17 ], concerns relating to body image, femininity, altered physical appearance, and self-confidence [ 18 ] are among the needs experienced by breast cancer survivors. In 2023, a systematic study on the needs of breast cancer survivors showed that most of these patients had psychological and informational needs [ 19 ]. In assessing the needs of BCSs, it is essential to consider culture, ethnicity, socioeconomic status, birthplace, and native language.…”
Section: Introductionmentioning
confidence: 99%